What will future physicians do when they face with ethical dilemmas? An overview of forensic medicine internship guidance - Yıldız, Abdulkadir; Gürpınar, Süleyman Serhat; Eroğlu, İbrahim; Cinkara, Osman; Aldemir, Fatma Nur (The Bulletin of Legal Medicine, 2022)
Objective: In this study, the guidance of forensic medicine education to medical students on ethical dilemmas and its effect on their attitudes and behaviours on ethical approach were examined, at the same time, common ethical dilemmas tried to be solved through discussion.Methods: A survey, trying to determine the attitudes and behaviors of the students in the face of possible scenarios including ethical dilemmas in their medical professional life, was applied on 111 volunteer participants covering fifth semester medical students. “SPSS for Windows 17.0” package program was used to analyze the acquired data.Results: It was observed that medical faculty students taking forensic medicine internship training stated that they would present a statistically significant level of ethical approach compared to those not taking forensic medicine internship training in all six scenarios with ethical dilemma (Scenarios 1, 2, 4, 5, 6 p
Keywords: Ethical dilemmas; Forensic medicine; Law; Human rights; Curriculum